Keanekaragaman Dan Kepadatan Gastropoda Di Perairan Desa Morindino Kecamatan Kambowa Kabupaten Buton Utara - Ira, Ira; Rahmadani, Rahmadani; Irawati, Nur (AQUASAINS, 2015)
Gastropods have important economic value because the shell can be used for a variety of decorations are expensive and the meat as a source of food. Gastropods also a key organism in the food chain in aquatic ecosystems. This research aims to determine the diversity and density of gastropods and environmental conditions that affect gastropods. The usefulness of the research is as information for the relevant agencies and parties that need as well as information for further research. The research was conducted in morindino village watersfrom August to October 2014. The placement transect squared/plots based on the state of the substrate is sandy and rocky beaches. The results found 20 species of gastropods which belong to 17 genera in 16 families. Density on the rocky shore organisms higher than the sandy beach that is 29.11 ind/m2 while the sandy beach that is 1.44 ind/m2. Rocky shore species diversity in higher at 1.8742 while the lower sandy beach which is 1.5858. However overall, the diversity of marine gastropods in Morindino village water was included in the medium category. Water velocity Parameter affects the density and diversity of gastropods.